Probe device for electrical measurements of parameters thin doped films ZnO - A. I. Blesman; R. B. Burlakov (Омский научный вестник)
Probe device for electrical measurements of parameters thin doped films ZnO is considered. On the base of use of this probe device there is measured by the Hall E ffect method the concentration of electrons of the conductivity in indium doped thin films ZnO with thickness in the interval (0,065–0,3) μm concentration of electrons of the conductivity in the interval (2–3,4)∙1019 cm–3 and low mobility of electrons of the conductivity — (4–8,5) cm2 /B∙s. Dignity of probe device is a possibility of the reduction of the voltage asymmetry of hall probes.